INCRETIN-BASED PHARMACOTHERAPY FOR OBESITY: A COMPARATIVE NARRATIVE REVIEW OF GLP-1, DUAL AND TRIPLE AGONISTS AND COMBINATION THERAPIES - Łukasz Krzystek; Karolina Buć; Paweł Buć; Michał Mazurek; Jagoda Józefczyk; Konrad Zieliński; Karolina Ganczar; Stanisław Jurkowski; Marianna Rudzińska; Mikołaj Zalewski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Incretin-based pharmacotherapy has emerged as a central component in modern obesity management. Recent developments include ont only GLP-1 receptor agosnists byt albo dual GIP/GLP-1 agonists, triple multi-rceptor agnosits and combination regimens integrating complementary hormonal pathways. Aim: The narrative review provides a comparative analysis of current incretin-based therapies for obesity, summarizing clinical evidence on their efficacy, safety and mechanisms of action. Methods: A structured literature search was conducted using PubMed, Scopus and Web of Science. The review included randomized controlled trials, original research articles, meta-analyses and selected narrative reviews addressing GLP-1 receptor agonists, dual GIP/GLP-1 agonists, triple agonists and combination therapies. Case reports, small uncontrolled studies and non-peer-reviewed sources were excluded. Results: GLP-1 receptor agonists, such as liraglutide and semaglutide, demonstrate consistent weight-reducing effects and metabolic benefits. Dual agonists, particularly tirzepatide, show enhanced efficacy, likely due to synergistic modulation of GIP and GLP-1 pathways. Triple receptor agonists, such as retatrutide, achieve the most pronounced reductions in body weight reported to date in pharmacotherapy. Combination therapy with semaglutide and cagrilintide provides clinically meaningful weight loss comparable to multi-receptor agonists. Across therapeutic classes, gastrointestinal adverse events remain the most common limitation. Conclusions: Incretin-based therapies represent a rapidly evolving field, with multi-receptor agonists and combination approaches offering the strongest therapeutic potential. Long-term studies are required to evaluate durability of outcomes and to better define patient phenotypes best suited for specific treatment strategies.